Humane Insight : Looking at Images of African American Suffering and Death - Baker, Courtney (Book collections on Project MUSE., 2015)
In the history of black America, the image of the mortal, wounded, and dead black body has long been looked at by others from a safe distance. Courtney Baker questions the relationship between the spectator and victim and urges viewers to move beyond the safety of the 'gaze' to cultivate a capacity for humane insight toward representations of human suffering.